DEVELOPMENT OF UNIVERSITY EDUCATION: STUDYING BASED ON RESEARCH - Kozak, Liudmyla V. (Educological discourse, 2016)
The article proposed the relevance of studying based on research in the context of solving problems and improving the quality of university education; essence and main ideas of studying based on research and its place in the training of future professionals; Foreign experience on methods effective combination of teaching and research and models of integration of research into the educational process; The features of forms of research work of students throughout the period of study at the university.